2020
DOI: 10.3390/cells9030746
|View full text |Cite
|
Sign up to set email alerts
|

Elevated PDK1 Expression Drives PI3K/AKT/MTOR Signaling Promotes Radiation-Resistant and Dedifferentiated Phenotype of Hepatocellular Carcinoma

Abstract: Resistance to radiotherapy (IR), with consequent disease recurrence, continues to limit the efficacy of contemporary anticancer treatment for patients with hepatocellular carcinoma (HCC), especially in late stage. Despite accruing evidence implicating the PI3K/AKT signaling pathway in cancer-promoting hypoxia, cancerous cell proliferation and radiotherapy-resistance, it remains unclear which molecular constituent of the pathway facilitates adaptation of aggressive HCC cells to tumoral stress signals and drives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 32 publications
2
73
0
Order By: Relevance
“…This involves, for example, IR-resistant forms of hepatocellular carcinoma. In this indication, the appearance of poorly differentiated, stem cell like features coincides with enforced AKT signaling, a joint induction of SOX2 and p53 mRNAs, and enhanced repair mechanisms to resolve IR-imposed DNA lesions [ 149 ]. Taken together, the interplay of PI3K/AKT and p53 in cancer presents highly divergent.…”
Section: P53 Mutant-dependent Impaired Apoptosis and Pi3k/akt Enfmentioning
confidence: 99%
“…This involves, for example, IR-resistant forms of hepatocellular carcinoma. In this indication, the appearance of poorly differentiated, stem cell like features coincides with enforced AKT signaling, a joint induction of SOX2 and p53 mRNAs, and enhanced repair mechanisms to resolve IR-imposed DNA lesions [ 149 ]. Taken together, the interplay of PI3K/AKT and p53 in cancer presents highly divergent.…”
Section: P53 Mutant-dependent Impaired Apoptosis and Pi3k/akt Enfmentioning
confidence: 99%
“…PI3K/Akt and mTOR signaling pathways are essential for maintaining the proliferation and survival of cancer cells (54). A recent study has shown that activation of PI3K/AKT/mTOR signaling increases hepatocellular carcinoma resistance to radiotherapy (55). On the one hand, activation of the PI3K/Akt pathway leads to the transcriptional activity of NFÎșB (56).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its important role in the Warburg effect, HK2 can directly interact with HIF-1α, and this mortalin-mediated interaction, occurring at the outer membranes of mitochondria, modulates the voltage-dependent anion-selective channel 1 (VDAC1) activity to preserve hypoxia-stressed cancer cells from apoptosis [ 40 ]. As a result of hypoxia-induced energy metabolism reprogramming, the augmented PDK1 expression in hypoxic tumors can drive the PI3K/Akt/mTOR signaling that promotes the EMT and formation of the radioresistant CSC-like phenotype, as it was shown for PDK1-overexpressing hepatocellular carcinoma [ 120 ]. Another glycolytic enzyme, fructose-bisphosphate aldolase A, was shown to be induced by hypoxia in colorectal cancer cells and correlated to their chemo- and radioresistance and, also, to a poor prognosis [ 121 ].…”
Section: Hypoxia-induced Reprogramming Of Energy Metabolismmentioning
confidence: 99%